Measuring Quality of Military Equipment. Issue 1 (2nd January 2022) - Olsson, Per
ABSTRACT: This article aims to present and discuss a method for estimating military equipment quality, while also comparing this approach to previous methods developed with the same purpose. Using main battle tanks as an example, the suggested method's structure and preliminary results are presented while its potential merits and limitations are also discussed. Preliminary results of the method show that US and western European tanks have traditionally had an qualitative edge. However, they also suggest that modern Russian and Chinese tanks have narrowed this gap. Equipment performance models, such as the one presented in this article, could provide additional insights when assessing the global and regional power balances as well as when estimating purchasing power parities and equipment cost escalation. This article will hopefully encourage further discussion on how to measure and compare military equipment quality.